Eukaryotic DNA replication : a practical approach - Cotterill, Sue (Practical approach series ;, 1999)
"Eukaryotic DNA Replication: A Practical Approach is a unique and very timely practical manual for researchers in this major subject area. Its eleven chapters provide a fully comprehensive and detailed description of current methods for studying key events during DNA replication." "In total, this volume provides over 120 tried and tested protocols for the analysis of eukaryotic DNA replication. Each protocol is described in a clear step-by-step format with copious hints and tips for success. As such, Eukaryotic DNA Replication: A Practical Approach is an essential bench manual for all cell biologists, biochemists and medical researchers interested in studying DNA replication."--Jacket